TOXICOLOGICAL EVALUATIONS OF TREATED COSMETIC EFFLUENT ON CLARIAS GARIEPINUS (THE AFRICAN SHARPTOOTH CATFISH) - T. O Sogbanmu; K. A Bawa-Allah; D. F Oroboade (UNILAG Journal of Medicine, Science and Technology, 2019)
The preponderance of industrial activities has led to the discharge of often untreated effluents intothe aquatic environment. Some industries endeavour to carry out some form of treatment on theireffluent before discharge into the environment; however, there is need to determine the efficiencyof such treatment by evaluating potential biological effects in aquatic organisms. In this study, weinvestigated the physico-chemical parameters of a treated cosmetic effluent as well as thebiochemical and histological effects of sublethal concentrations of the effluent in Clariasgariepinus (The African sharptooth catfish) over a period of 28 days. Some physico-chemicalparameters including zinc and lead were higher than the Federal Ministry of Environment setlimits while others such as phthalate, triclosan and parabens were not detected. The median lethalconcentration of the effluent to C. gariepinus was 4.14 mL/L (0.41%). Significant changes(p≤0.05) were observed in the levels of reduced glutathione and malondialdehyde in the liver of C.gariepinus exposed to sublethal concentrations of the treated effluent compared to control after 14and 28 days of exposure. Histological alterations observed in C. gariepinus exposed to sublethalconcentrations of the treated effluent were shortening/blunting of secondary lamellae in the gillsand hepatic central veins infiltrated with red blood cells in the liver. The results show that longterm exposure to sublethal concentrations of the treated cosmetic effluents may cause deleteriouseffects to animals inhabiting recipient freshwater ecosystems. Further studies to explore otherpotential biological effects of treated cosmetic effluents are recommended in order to provideholistic and evidence-based information to relevant stakeholders and environmental regulatoryagencies.